The serum level alterations of Acute-phase proteins, serum alpha-1-acid glycoprotein, haptoglobin and alpha-2-Macroglobulin in the Patients with Stage I of Multiple Myeloma - sonya mahabadi; mohamadhasan khadem ansari; Fatemeh Kheradmand; Youssef Rasmi (Journal of Research in Applied and Basic Medical Sciences, 2020)
Background & Aims:  Acute phase proteins are mainly synthesized by the liver and macrophages in inflammatory conditions as a result of various traumas and malignancies. Increased levels of these proteins have been reported in many tumors like multiple myeloma as an important indicator for the prognosis of malignancies. We investigated the serum levels of acute phase proteins in multiple myeloma cancer patients in stage one due to the important role of these proteins in malignancies. Materials & Methods: The serum levels of acute phase proteins (alpha 1-acid glycoprotein, haptoglobin and alpha-2-Macroglobulin) were measured in 30 patients with stage I of multiple myeloma and 30 healthy persons as the control group. The average age of population was 69 years. Measurement of the serum levels of proteins was done using Capillary zone electrophoresis and high resolution (HR). Total protein amounts were measured by biuret method, as well. The data were analyzed by SPSS method. Results:  The values obtained from results of the test and statistical calculations in the groups of study suggested that the serum levels of examined acute phase proteins decreased significantly in the patients compared to the control group. (P<0.001) Conclusion: The results of this study indicated the reduction of serum alpha-1-acid glycoprotein, haptoglobin and alpha-2-Macroglobulin in stage I patients compared to the control group, which is inconsistent with previous studies. These proteins may be considered as specific prognostic and diagnostic factors in multiple myeloma stage I. However, further studies are needed to assess accurate results.